South African accounting students’ perceptions on soft skills development in an interdisciplinary case study - Mostert, Sarina; van Wyk, Milan; Wessels, Riaan (Frontiers in Education, 2025)
IntroductionSoft skills have become a focus area for developing university students to meet the needs identified by future employers and to be employable in an ever-changing workplace. In response, professional bodies such as the South African Institute for Chartered Accountants (SAICA) have introduced guidance frameworks to identify the key skills required. Universities use these frameworks to identify developmental areas to equip students for future employment.MethodsA multidisciplinary work-integrated group project was developed by a resident university in South Africa to develop skills that are consistent with the framework developed for the Associated General Accountant designation (AGA(SA)) offered by SAICA. The students solved ‘real-life’ problems, submitted a group written report and presented a practical solution to a panel consisting of lecturers, alumni and stakeholders in industry. The purpose of this study was to understand how students perceive the development of specific soft skills by contrasting their perceptions of their skills before and after the project with a self-developed questionnaire using a Likert scale, supplemented by open-ended questions. The data was analysed using descriptive statistics, ANOVA and thematic content analysis.ResultsThe findings of the study identified that the students perceived that certain soft skills were developed during the project. Most of these skills related to interpersonal soft skills such as teamwork, communication, relationship building and management of team members. Critical thinking and problem-solving skills were also developed through the project.DiscussionThe result from the study contributes towards the literature on how an interdisciplinary work-integrated case study can contribute towards the development of soft skills for postgraduate students. The research particularly highlights the importance of the development of interpersonal soft skills, which is essential in the workplace.